THE ROLE OF MANAGEMENT INFORMATION SYSTEMS IN INDUSTRY TRAVELOKA STARTUP - Maya Tika Zulkarnain; Dewi Puspaningtyas Faeni (IJESM Indonesian Journal of Economics and Strategic Management, 2024)
This research aims to see the extent of implementation of management information systems. This research focuses on the startup company Traveloka. This research uses a literature study approach which uses credible sources to conclude related findings and strengthen this research. The results of this research explain that SIM helps Traveloka manage the ordering process, data analysis, product development, inventory management, customer management, data security and financial management more efficiently and effectively. Although there are several obstacles that may be associated with SIM implementation, such as integration complexity, infrastructure limitations, data security, technological changes, and user training, Traveloka can overcome them with the right approach and the necessary investment